A colonização de uma área por espécies de abelhas sem ferrão. Um estudo de caso: Partamona helleri (Friese, 1900) (Hymenoptera : Apidae: Meliponini) - Ferreira, Kátia Maria (Universidade Federal de São Carlos, 2011)
Bees are obligatory floral visitors and are considered the main pollinators of angiosperms. The increasing interest in the services of bees has led to efforts to develop management strategies for conservation purposes. The sustainable use of pollinators requires knowledge on the regional diversity of floral visitors obtained from the identification of the agents responsible for the effective pollination of crops. Furthermore, understanding the reproductive biology and population structure of these species as well as the factors that enable the colonization of certain areas by a species of bee are necessary requirements to designing management and conservation strategies. To test the hypothesis that a certain area may be colonized by a small number of maternal lineages of female founders of a species of stingless bee, samples from 73 nests of Partamona helleri (Hymenoptera: Apidae: Meliponini) located on the Brazilian campuses of the Universidade Federal de São Carlos (UFSCar, n = 34), Universidade de São Paulo in São Paulo (USP-SP, n = 14) and Universidade de São Paulo in Ribeirão Preto (USP-RP, n = 25) were analyzed for two mitochondrial genes cytochrome b (cyt b) and cytochrome oxidase I (COI) in order to determine the number of different haplotypes. A fragment of the cytochrome b (485 bp) and cytochrome oxidase (611 bp) genes was sequenced for all nests sampled. The analysis of nucleotide sequences identified only one cyt b haplotype in samples from UFSCar and a second haplotype, distinct from the former by a base substitution, in samples from USP-SP, while samples from USP-RP exhibited three distinct haplotypes, one of which was shared by the samples from UFSCar. Among the nucleotide substitutions, some resulted in amino acid changes in the product of the cyt b gene. A similar result was observed with the COI gene. Fst values estimated for the mitochondrial DNA from the cyt b and COI genes were 31.8% and 36.1%, respectively. The estimated rate of nucleotide substitution for cyt b was higher than that found for COI. Thus, the former gene was found to be less conserved than the latter in stingless bees. The larger number of haplotypes observed in the samples from USP-RP may be due to the introduction of colonies from other regions of the country. To determine the occurrence of population structure for nuclear genes, the samples were also examined for several microsatellite loci. Among the 18 heterologous microsatellites loci tested, only four Mbi215, Mbi278, Mbi232 and Mbi254 exhibited genetic variation. The prospection of species-specific microsatellite loci for Partamona helleri using the enrichment method for the construction of DNA libraries allowed characterizing seven new loci. Samples from 73 nests (two workers per colony) were analyzed for eleven microsatellite loci. The populations exhibited significant differentiation (Fst = 0.129, P = 0.000). Fst values estimated for mitochondrial genes and nuclear genes (microsatellites) were compared to establish whether there is evidence for differential male and female dispersal ability in this species. No evidence was found of sex-asymmetrical dispersal (colonizing females are colonizers; males are dispersers). Analysis of phenotypic segregation in the progenies of several nests revealed the occurrence of monandry in the species studied and, consequently, a simple sociogenetic structure monogyny/monandry. The presence of 'foreign' workers was rarely observed in the nests analyzed.
Keywords: Genética de populações; Microssatélite; Variabilidade genética; DNA mitocondrial; Haplótipos; Partamona helleri; Mitochondrial DNA; Microsatellite; Genetic variation; Population structure; CIENCIAS BIOLOGICAS::GENETICA